Decoupling design and kinematic analysis of rope driven flexible wheelchair manipulators - WANG Lu; ZHAO Dongjie; ZHANG Weitao; WANG Yini; ZHANG Kun (Jixie chuandong)
ObjectiveAiming at the problems of large size, heavy weight and safety of human-machine interaction of traditional rigid wheelchair manipulators, a 6-degree-of-freedom rope driven flexible wheelchair manipulator was designed.MethodsThe manipulator adopted a flexible translation structure, which can keep the end posture unchanged while changing the end position, realized the decoupling of position and posture, and effectively improved the rigidity of the flexible manipulator. The kinematic model of the flexible manipulator was established based on the constant curvature modeling method, and the kinematic analysis between the drive space, joint space, and operation space as well as the decoupling analysis between each flexible joint were carried out. A simulation model based on Adams virtual prototype was established.ResultsBy comparing with the numerical simulation results of Matlab software, the accuracy of the kinematic algorithm is verified, which provides a basis for the subsequent motion control of the manipulator.